Ureditev minimalne plače na ravni EU - Bobovnik, Andraž (Delavci in delodajalci, 2019)
According to the announcement of the new President of the European Commission Ursula von der Leyen and the strengthening of the EU's social dimension at the end of 2019 and at the beginning of 2020, we expect an initiative from the European Commission to establish a European minimum wage framework. The paper presents the situation in this area in the individual Member States, the EU's competences, past initiatives, the views of key players and possible future scenarios in regulating the issue of a minimum wage at EU level.
Keywords: competence of the EU; človekove pravice; delovno pravo; European Commission; European Pillar of Social Rights; Evropska unija; minimalna plača; minimum wage; social dialog; socialna varnost